Cerebral blood flow increases in idiopathic generalized epilepsy and its relationship with mood dysfunction - Yun Lien; Ayushe A. Sharma; William R. Willoughby; Anna Moyana; Jennifer Pilkington; Ja’ Kaiya Bryant; Adam M. Goodman; Goutham Selladurai; Lawrence W. Ver Hoef; Jerzy P. Szaflarski; Jane B. Allendorfer (Epilepsia Open)
Abstract Objective To investigate the relationship between cerebral blood flow (CBF), seizure control, and mood regulation in idiopathic generalized epilepsy (IGE), we hypothesized that higher CBF in mood‐regulating regions would be associated with greater mood disturbance, particularly in patients with poor seizure control. Methods Twenty‐three patients with IGE (13 female) and 19 healthy controls (HCs; 9 female) completed 3T MRI. Patients with IGE were categorized into those with seizures controlled for >6 months (IGE−) and those with ≥1 seizure in the last 6 months (IGE+). Participants completed the Profile of Mood States, with the Total Mood Disturbance (TMD) score indexing the current overall mood state. A pulsed arterial spin labeling (PASL) MRI sequence was used to measure CBF. Average CBF within emotion‐related brain regions was estimated. One‐way ANOVA tests examined the main effect of group and seizure control on CBF and TMD. Pearson correlation analyses identified relationships between CBF and TMD in the combined sample and individual groups (significant at FDR‐corrected p < 0.05). Results Compared to HCs, IGE exhibited significantly higher TMD (mean ± SD: IGE = 57.39 ± 32.32, HC = 2.05 ± 19.86; p < 0.001) and CBF (mean ± SD: IGE = 60.20 ± 10.88, HC = 53.45 ± 10.22; p = 0.046). However, no statistically significant differences in TMD were observed between IGE+ and IGE−, although both demonstrated significantly higher TMD than HCs (both p < 0.001). Additionally, no statistically significant effect of seizure control was found on CBF. In the combined groups, TMD and CBF showed a positive correlation (r = 0.36, p = 0.019). Significance This is the first study to investigate the relationship between mood disturbance, seizure control, and CBF in IGE. Both neurobiological and mood state measures showed significant differences between IGE patients and HCs. The relationship between greater CBF and worse mood states (higher TMD) suggests changes in CBF may be a potential biomarker for mood disturbance in epilepsy. Larger studies investigating the effects of seizure control on CBF are needed to clarify this relationship in IGE. Plain Language Summary Patients with idiopathic generalized epilepsy (IGE) often experience mood comorbidities, such as depression and anxiety. This study aimed to investigate whether cerebral blood flow (CBF) could serve as a potential biomarker for mood disturbance in IGE. We found that patients with IGE had higher CBF and greater mood disturbance compared to healthy individuals, and that higher CBF was associated with worse mood across all participants. Our findings suggest that CBF may be a useful biomarker for mood state, providing insights that could improve the mental health outcomes for patients with IGE. However, larger studies that better account for seizure frequency are needed to assess the effects of seizure control on CBF.